Food Security Monitoring in the Republic of Belarus - Kandratsenka, Sviatlana (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
The article investigates theoretical and methodical aspects of food security monitoring and reveals significant development tendencies in the world market of food and agricultural raw materials. It also discusses the experience of the Republic of Belarus in the assessment level for physical and economic food availability to the population. The monitoring algorithm of national food security of the Republic of Belarus including assessment criteria, indicators and their liminal values, and an information support model is presented. The monitoring algorithm assumes complex application of techniques adapted for social and economic conditions of the Republic, including tendencies assessment and development factors of the world market food security level and independence, threats on life quality of the population, and methodical recommendations about ensuring stability of food security. The applied system of basic indicators and their threshold values allows the creation of a full picture of security and threats from different directions, and ways of developing mechanisms to deal with them.